A Method to Quench Carbodiimide‐Fueled Self‐Assembly. Issue 1 (24th August 2020) - Schnitter, Fabian; Boekhoven, Job
Abstract: In chemically fueled self‐assembly, the activation and deactivation of molecules for self‐assembly is coupled to a reaction cycle. In biological examples, these reactions are typically fast, such that the building blocks remain activated for mere seconds. In contrast, synthetic reaction cycles are slower for self‐assembly, i. e ., with half‐lives on the order of minutes. In search of life‐like, dynamic behavior in synthetic systems, several groups explore faster reaction cycles that form transient labile building blocks with half‐lives of tens of seconds. These cycles show exciting properties, but brought about a new challenge, i. e ., accurately analyzing the fast cycle is impossible with classical techniques. We thus introduce the notion of quenching chemical reaction cycles for self‐assembly. As a model, we use the fast carbodiimide‐fueled chemical reaction cycle and demonstrate a method that quenches all reactions immediately. We show its accuracy and demonstrate the application for several reaction cycles and a range of dissipative assemblies. Finally, we offer preliminary design rules to quench other chemically fueled reaction cycles. Abstract : Counting bricks in the wall : Chemically fueled assemblies are regulated by a chemical reaction cycle. A fast reaction cycle was recently introduced that shows exciting, dynamic self‐assembly behavior. However, analysis of its kinetic properties is challenging due to its speed. Thus, we introduce a simple, powerful method to quench all reactions in the reaction cycle. We show the accuracy and application for several reaction cycles and a range of molecular assemblies.